The predictive effects of foreign language enjoyment, anxiety, and boredom on general and domain-specific English achievement in online English classrooms - Xinpeng Wang; Yi Li (Frontiers in Psychology, 2022)
This non-experimental study employed three questionnaires adopted from and validated by prior studies. To carry out the study, an electronic survey created through Wenjuanxing, a computer program for conducting an online survey in China, was employed and convenience sampling technique was used. Guided by the control-value theory of educational psychology, as well as the broaden-and-build theory and the well-being theory of Positive Psychology, this questionnaire study investigated 880 non-English major freshmen’ foreign language enjoyment (FLE), foreign language class anxiety (FLCA), and foreign language boredom (FLB) in online English courses, as well as their correlations. Also measured were their joint predictive effects on the general and domain-specific learning outcomes of online English classrooms (reading-to-writing group and speaking group). With statistical analysis carried out by SPSS 26.0 and AMOS 23.0, the results showed that: (1) learners had relatively high levels of FLE and FLCA, but a medium level of FLB; (2) a small negative correlation was found between students’ FLE and FLCA, a medium to high negative correlation between FLE and FLB, and a small to medium positive correlation between FLCA and FLB; FLE has a significant positive correlation with learners’ actual performance and self-perceived performance, while FLCA and FLB have a significant negative correlation with both; and (3) After entering the same regression model, all three emotions have a significant predictive effect on learners’ self-perceived performance while only FLE and FLCA had a significant predictive effect on their actual performance in the online context. Domain-specifically, the reading-and-writing group demonstrated similar trends while there were no significant correlations between emotions and actual performance in the speaking group. The findings can provide pedagogical implications for online foreign language teaching and theoretical contribution to foreign language emotion research.